2020
DOI: 10.3390/insects11050317
|View full text |Cite
|
Sign up to set email alerts
|

Nest Entrances, Spatial Fidelity, and Foraging Patterns in the Red Ant Myrmica rubra: A Field and Theoretical Study

Abstract: The nest architecture of social insects deeply impacts the spatial distribution of nestmates their interactions, information exchanges and collective responses. In particular, the number of nest entrances can influence the interactions taking place beyond the nest boundaries and the emergence of collective structures like foraging trails. Here, we investigated in the field how the number of nest entrances impacted the foraging dynamics of Myrmica rubra ant colonies. We located the nest entrances where recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Besides the social information mediated by pheromone trails, ant individuals improve their navigational skills over successive foraging trips 21 and may eventually develop a fidelity to stable and rewarding food sites. Such a site fidelity has been observed in many different ants such as ponerine ants ( Dinoponera quadriceps 22 ), harvester ants ( Pogonomyrmex occidentalis 15 ; Pogonomyrmex barbatus 23 ) , formicine ants (F ormica schaufussi 24 ; Lasius niger 20 , 25 ) and myrmicine ants ( Myrmica rubra 26 ). Route learning coupled to fidelity to a foraging site minimizes the travel time, reduces the likelihood of foragers to be lost, speeds up the dynamics of food exploitation and eventually favours the choice of this site by the whole colony.…”
Section: Introductionmentioning
confidence: 76%
“…Besides the social information mediated by pheromone trails, ant individuals improve their navigational skills over successive foraging trips 21 and may eventually develop a fidelity to stable and rewarding food sites. Such a site fidelity has been observed in many different ants such as ponerine ants ( Dinoponera quadriceps 22 ), harvester ants ( Pogonomyrmex occidentalis 15 ; Pogonomyrmex barbatus 23 ) , formicine ants (F ormica schaufussi 24 ; Lasius niger 20 , 25 ) and myrmicine ants ( Myrmica rubra 26 ). Route learning coupled to fidelity to a foraging site minimizes the travel time, reduces the likelihood of foragers to be lost, speeds up the dynamics of food exploitation and eventually favours the choice of this site by the whole colony.…”
Section: Introductionmentioning
confidence: 76%
“…The effect of changing space constraints on encounter rate regulates nest construction ( Halley et al 2005 , Gravish et al 2013 ). The relation between path shape, density, and encounter rate also explains why nest connectivity affects the probability that recruiting ants will encounter others and draw them into a task ( Pinter-Wollman et al 2012 , Lehue et al 2020 ).…”
Section: Encounter Rate As a Cue For Densitymentioning
confidence: 99%
“…Further, during the laboratory experiment, contrary to the prediction, the colonies frequently inhabited the sites with two entrances and used both. No data were obtained to show if the nest sites with two entrances are better; however, many ant species use nests with single or multiple entrances, where the number of entrances can be diverse even inside the nests of one species (e.g., [38][39][40][41]). Using entrances from two opposite sites could have an influence on the foraging activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that for the red ant Myrmica rubra, the number of nest entrances influenced the collective foraging of the colony: multiple nest entrances reduced the foraging efficiency [42] but favored the simultaneous exploitation of several sources. It has been suggested that multiple entrances appear as a way for small-or medium-sized colonies to benefit from some of the advantages conferred by polydomy [38]-i.e., the simultaneous use of several nest sites by one colony-and T. crassispinus colony might use more than one nest (seasonal polydomy) [43]. It would be interesting to check if, for small colonies like those of Temnothorax ants, the effect of two entrances vs. one entrance on foraging is visible.…”
Section: Discussionmentioning
confidence: 99%